APPLICATION OF INDICATIVE QUALITY INDICATOR IN DYNAMIC MANAGEMENT OF THE TOPOLOGY OF A DISTRIBUTION NETWORK WITH LOCAL ENERGY SOURCES WITH THE PURPOSE OF MINIMIZING ENERGY LOSSES - YATSENKO, Dmytro; POPOV, Vladimir; ZAMULKO, Anatolii; YARMOLIUK, Olena; ADANIKOV, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In practically all countries, a significant part of distribution electric networks is operated in an open mode. Therefore, the task of choosing the optimal topology of the electrical network remains relevant and popular among researchers. To date, many ways of solving this problem have been proposed, which have been reflected in hundreds of publications. To achieve the goal of forming the optimal topology of the electric network, various optimization methods are used, the problem is also solved in both single-criteria and multi-criteria formulations. In this article, a bibliographic analysis is carried out and the use of an indicative qualitative indicator is proposed for finding the optimal topology of the distribution electric network in real time, which makes it possible to minimize the loss of active energy. Currently, this is relevant due to the growth of load heterogeneity and the increase in the share of local energy sources in the distribution networks of our country. These factors form flow distributions daily, which in most cases will not coincide with the mode for which the appropriate network configuration was chosen, which in turn leads to an increase in electrical energy losses. The effect of the proposed approach depends on the proper level of technical and information support of the network, especially since most of the equipment of distribution electric networks has exhausted its physical resource. The use of an indicative qualitative indicator is envisaged in distribution networks equipped with modern switching devices with the possibility of remote control and the presence of systematic measurements of the mode parameters of the network. Based on the obtained research results, it can be concluded that the developed indicative indicator is successfully used in solving the problems of finding the optimal network topology in real time, which makes it possible to achieve significant results. additional reduction of active energy losses.